2020
DOI: 10.1177/0004563220981106
|View full text |Cite
|
Sign up to set email alerts
|

Development of a high-throughput SARS-CoV-2 antibody testing pathway using dried blood spot specimens

Abstract: Background: Serologic assays for Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) have roles in seroepidemiology, convalescent plasma-testing, antibody durability and vaccine studies. Currently, SARS-CoV-2 serology is performed using serum/plasma collected by venepuncture. Dried bloodspot (DBS) testing offers significant advantages; as it is minimally invasive, avoids venepuncture with specimens being mailed to the laboratory. Methods: A pathway utilising a newborn screening laboratory infrastruct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(51 citation statements)
references
References 25 publications
3
47
0
Order By: Relevance
“…Several parameters affect the amount of predicted elution from the filter cards [ 26 , 28 , 49 ]. The number of circles spotted with blood, the punch size, and the number of punches will determine the size of the surface area exposed to elution buffer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several parameters affect the amount of predicted elution from the filter cards [ 26 , 28 , 49 ]. The number of circles spotted with blood, the punch size, and the number of punches will determine the size of the surface area exposed to elution buffer.…”
Section: Discussionmentioning
confidence: 99%
“…We found modifications of the standard procedure had limited impact on the performance of DBS, but overall, we found that 10 spots from 5 cards eluted in 750 µL of PBS gave the most consistent results. A recent study also showed the effect of DBS size and punch location on the observed DBS signal [ 26 ]. DBS specimens have been shown to be stable at room temperature, 4 °C and −20 °C, at ambient or low humidity conditions for at least 28 days [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An in-house direct ELISA was developed as previously described (16)(17)(18)(19), with some modifications. Maxisorp (Nunc, Loughborough, UK) 96-well plates were coated with RBD protein (recombinantly generated in a mammalian expression system, in house) at 2 µg/ml in bicarbonate buffer, pH 9.6 at 4°C overnight; wells were blocked for 1 hour at room temperature with 3% w/v non-fat dried milk powder (Sigma Aldrich, # 70166-500G) in phosphate-buffered saline containing 0.1% Tween 20 (PBS-T), washed in PBS-T. Dilutions of patient sera (1 in 50 in 1% Milk PBS-T), were added in duplicate to wells coated with RBD protein and incubated for 2 hours at room temperature.…”
Section: Detection Of Anti-sars-cov-2 Rbd Igg Antibodiesmentioning
confidence: 99%
“…Several other studies in different populations, such as health care workers, key workers, athletes and children have evaluated DBS sampling for SAR-CoV-2 antibody testing (6)(7)(8)(9)(10)(11)(12)(13)(14). In these studies, similar test characteristics were reported with a sensitivity ranging from 89 up to 100% and a specificity of 100% (7,10,11), or, reported a nearly perfect agreement in SARS-CoV-2 antibody detection between DBS samples and paired venous blood samples (6,9,(12)(13)(14). However, some studies were limited by the lack of serum serology as a reference test (7,8) or the rather limited sample size (i.e., <50 positives as assessed by the reference test) (6,7,11,12).…”
Section: Discussionmentioning
confidence: 99%